Effects of elevated CO2 on Stipa baicalensis photosynthesis depend on precipitation and growth phase. Issue 6 (30th September 2019) - Wang, Hui; Zhou, Guangsheng; Jiang, Yanling; Shi, Yaohui; Xu, Zhenzhu
Abstract: Elevated atmospheric CO2 concentration and simultaneous precipitation change affect plant physiology and growth either directly or indirectly. The main objective of this study was to investigate the effects of elevated CO2 and precipitation change, alone or in combination, on photosynthesis and growth in Stipa baicalensis under differential growth phases. Elevated CO2 showed a consistently significant increase in net photosynthesis rate ( A net ), water‐use efficiency (WUE), leaf area and biomass. However, elevated CO2 did not mitigate the negative effects of severe drought stress. Increase of A net under elevated CO2 attributed to C i in the early growth phase, but WUE and Rubisco carboxylation ( V cmax ) was the main inductor in the later growth phase. Effects of elevated CO2 on S. baicalensis were closely associated with precipitation conditions, and the influence on photosynthetic capacity was also related to the growth phase. Drought significantly reduced A net in June and August, increased WUE in June but did not show effect in August. Precipitation enhancement was beneficial to leaf area and biomass accumulation. Elevated CO2 and enhanced precipitation in combination promoted A net by 158% and 93.4% in June and August, respectively; moreover, their interaction increased the total biomass by 44.4%. Our results suggested that the elevated CO2 concentration in the future might be beneficial to the growth of S. baicalensis, but elevated CO2 influence on S. baicalensis might strongly depend on precipitation conditions and the growth phase. Abstract : Effects of elevated CO2 on Stipa baicalensis were closely associated with precipitation conditions and the growth phase. Increase of net photosynthesis rate ( A net ) under elevated CO2 attributed to intercellular CO2 concentration ( C i ) in the early growth phase and water‐use efficiency and Rubisco carboxylation ( V cmax ) in the later growth phase. Elevated CO2 and increased precipitation in combination promoted A net in June and August, however, did not mitigate the negative effects of severe drought stress.